Advanced Light Management for Encapsulated Silicon Solar Cells: An Antireflective Textured Film with a Down-Shifting Lead-free Perovskite Cs2AgxNa1-xBiyIn1-yCl6 Phosphor - Kong, Mengqin; Raievska, Oleksandra; Stroyuk, Oleksandr; Barabash, Anastasia; Wu, Zhenni; Tian, Jingjing; Erban, Christof; Osvet, Andres; Batentschuk, Miroslaw; Brabec, Christoph (ACS Applied Materials and Interfaces, 2024)
Light management (LM) is the key to the encapsulation of high-performance silicon (Si) photovoltaic devices (PVs). In this work, simulation analyses provide meaningful insights into optical losses and guide the improvement of the PV performance of the encapsulated silicon solar cells (Encap-Si SCs). An antireflective layer, textured polydimethylsiloxane (PDMS), is designed to reduce reflection losses, especially at a lower illumination intensity, thereby achieving an improvement of 10.89% in the short-current density (JSC) and hence 12.67% in the power conversion efficiency (PCE) when illuminated at an incident angle of 60°. Subsequently, a luminescence down-shifting material, lead-free Cs2AgxNa1-xBiyIn1-yCl6 (CANBIC) double perovskite phosphor, is incorporated into the PDMS film to further enhance the energy yield in the ultraviolet (UV) region. The textured PDMS film with an optimized CANBIC content ultimately achieves a significant improvement in PCE from 21.770 to 23.136%. This enhancement is attributed to the increase in JSC by 2.381 mA/cm2 due to the reduced reflection losses (by antireflective PDMS) and down-converted UV energy (by CANBIC), providing a remarkable advance in LM toward highly efficient encapsulated PVs.
CRIS-Team Scopus Importer:2024-08-23
Keywords: antireflective layer; down-shifting layer; encapsulated Si solar cell; lead-free perovskite phosphor; optical simulation